Preliminary Analysis of Irradiance Data for the Generation of a Typical Solar Radiation Year for Évora, Portugal - Canhoto, Paulo (2016)
This report presents the generation of a mean solar radiation year using the 2003-2015 data series of solar global and diffuse irradiances on a horizontal surface in Évora, Portugal. The selection of the months/years to be included in the mean solar radiation year is based on the simple comparison of the mean daily solar global irradiation of each month/year with the mean value of the entire series, for each month of the calendar. Additionally, the direct normal irradiance is estimated and compared with the measurements taken at the same location since 2015. These are preliminary results that will be extended in the next step to the generation of a Typical Solar Radiation Year and a Typical Meteorological Year for Évora.